Nancy Huston, Self-Translation and a Transnational Poetics (Ticontre. Teoria Testo Traduzione, 2014)
Nancy Huston (Calgary, 1953) is one of the francophone authors who contributed – with an essay entitled Traduttore non è traditore – to the theo- retical volume Pour une littérature-monde (Michel Le Bris and Jean Rouaud, 2007), which inscribes as an important step in the ongoing theoretical definition of world literature. With reference to a selection of Huston’s non-fiction publications, I am going to outline her poetics of self-translation and how the latter intimately relates to what she regards as the very task of Literature. Finally, I am going to briefly sketch the content of three of her novels: L’empreinte de l’ange/The Mark of the Angel (1998- 9), Lignes de faille/Fault Lines (2006-7) and Danse Noire/Black Dance (2013-14), which epitomize Huston’s transnational/translational poetics. The peculiar nature of the experience as a bilingual writer and self-translator opens to new possible prospects on the theorization of world literature, by question- ing the boundaries of linguistic and cultural identity and by defining an ethical aspiration for both literature and translation. Nancy Huston (Calgary, 1953) ha contribuito con il saggio Traduttore non è traditore alla raccolta Pour une littérature-monde (Michel Le Bris e Jean Rouaud, 2007), volume che costituisce una tappa significativa nella teorizzazione contemporanea sulla letteratura-mondo. Attraverso l’analisi di questa e di altre pubblicazioni, il presente articolo si propone di indagare la poetica di auto-traduzione della Huston, per mostrare come essa sia intimamente connessa a quella che l’autrice ritiene essere la funzione fonda- mentale della Letteratura. Vengono inoltre presi in considerazione tre dei suoi romanzi – L’empreinte de l’ange/The Mark of the Angel (1998-9), Lignes de faille/Fault Lines (2006-7) e Danse Noire/Black Dance (2013-14) – che incarnano, a livello di conte- nuti, tale poetica traduttiva e transnazionale. Riflettendo sulla particolarità della sua esperienza di scrittrice bilingue e autotraduttrice, Huston mette in discussione i confini dell’identità linguistica e culturale, fornendo così nuove prospettive al dibattito teo- retico sulla letteratura-mondo, e invocandone una missione etica.